2013
DOI: 10.1115/1.4023639
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Impulse Diagrams for Blast Loaded Continuous Beams Based on Dimensional Analysis

Abstract: This paper studies pulse loading shape effects on the dynamic response of continuous beams. The beam is modeled as a single span with symmetrical semirigid support conditions. The rotational spring can assume different stiffness values ranging from 0 (simply supported) to oo (fully clamped). An analytical solution for evaluating displacement time histories of the semirigidly supported (continuous) beam subjected to pulse loads, which can be extendable to very high frequency pulses, is presented in this paper. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…M. Li and Meng, 2002b;Nystrom, 2006;Campidelli and Viola, 2007;Fallah and Louca, 2007;W. Wang et al, 2012a;Fallah et al, 2013;Parlin et al, 2014;Chernin et al, 2016). This sensitivity can partially be considered by building additional curves reflecting the variation in a certain parameter, e.g.…”
Section: P-i Diagram Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…M. Li and Meng, 2002b;Nystrom, 2006;Campidelli and Viola, 2007;Fallah and Louca, 2007;W. Wang et al, 2012a;Fallah et al, 2013;Parlin et al, 2014;Chernin et al, 2016). This sensitivity can partially be considered by building additional curves reflecting the variation in a certain parameter, e.g.…”
Section: P-i Diagram Methodsmentioning
confidence: 99%
“…W. Ma et al, 2007;H. J. Shi et al, 2012;Fallah et al, 2013;Yu et al, 2018). The latter method is discussed in Sections 3.3 and 4.1.…”
Section: P-i Diagram Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ese P-I diagrams strongly depend on pressure versus time expression (pulse shape) of the explosion [10], and together with SDOF modelling, they are used to find the blast response of complex of structures, such as cablesupported facades [11]. Both SDOF-type model [12] and continuous beam model [13] are used for developing P-I diagrams. Recently, it is shown that batch finite element simulations [14] cannot lead to P-I diagram unless preliminary information regarding SDOF parameters is available.…”
Section: Introductionmentioning
confidence: 99%